2022
DOI: 10.1097/md.0000000000031323
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene citrate mild stimulation improved follicular development outcomes in PCOS women with high luteinizing hormone and poor ovarian response: A case report

Abstract: Introduction: Polycystic ovary syndrome (PCOS) is a main cause of anovulatory infertility in women of reproductive age. About 30% to 50% of patients with PCOS has high serum basal luteinizing hormone (LH) levels, and almost 5% of PCOS women with high LH have poor ovarian response (POR). We reported a case of a PCOS woman with high basal LH levels who canceled due to POR during two consecutive controlled ovarian stimulation treatments, which was considered to be related to the suppression of LH level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This is due to increased amplitude and frequency of LH pulses [ 20 ]. A recent study has shown that approximately 30% to 50% of patients with polycystic ovary syndrome have high serum basal LH levels and nearly 5% of women with high LH polycystic ovary syndrome have poor ovarian response [ 54 ]. In DOR patients, due to the decrease in the number of follicles, the insufficient secretion of estrogen and progesterone, and the weakening of negative feedback, the pituitary gland will secrete more FSH, resulting in an increase of the FSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to increased amplitude and frequency of LH pulses [ 20 ]. A recent study has shown that approximately 30% to 50% of patients with polycystic ovary syndrome have high serum basal LH levels and nearly 5% of women with high LH polycystic ovary syndrome have poor ovarian response [ 54 ]. In DOR patients, due to the decrease in the number of follicles, the insufficient secretion of estrogen and progesterone, and the weakening of negative feedback, the pituitary gland will secrete more FSH, resulting in an increase of the FSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a high proportion, some women with PCOS fulfill the POSEIDON group, particularly for Groups 1 and 2. However, there are limited data available regarding the pregnancy outcomes of women with PCOS classified as poor responders ( 17 , 18 ). There is no study to address LBR per fresh embryo transfer and CLBR per aspiration cycle for women with PCOS categorized as poor responders in fertility treatments.…”
Section: Introductionmentioning
confidence: 99%